Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Find (g∘k)(1)for g(x)=11x2−4x+6and k(x)=4x−11. (g∘k)(1)=

Sagot :

The first step you have to follow is to find k(1) by replacing each x in k(x) for 1:

[tex]k(1)=4(1)-11=4-11=-7[/tex]

Now, find g(k(1)), it means, g(-7):

[tex]g(-7)=11(-7)^2-4(-7)+6=573[/tex]

(g°k)(1)=573.